Press and political discourse at the dawn of the Republic in Peru. Approaches to the study of El Loro (1822) (Revista revoluciones, 2023)
The historiography on the independence process has been renewed and diversified in recent decades. Special interest has been taken in the study of the press as a representative of a political faction and, consequently, the analysis of its political discourse, as well as the identification of the communication networks and the spaces of sociability in which it circulated. For this reason, the political discourse of El Loro (1822) is analyzed to reflect on the political culture at the dawn of the Republic, because this historical source was one of the many ephemeral and rebellious newspapers, which formed an opposition faction of the republican model and He showed himself as a political actor in the intense ideological debate that took place in the public space on the government model that Peru should opt for after the departure of San Martín. The work is divided into two sections, it began with a historiographical balance on the press in the process of Independence and will culminate with the analysis of the following thematic axes: freedom of the press and public debate, the defense of a monarchical government, the delivery of Guayaquil and the representative government.
Keywords: political discourse; independence; Guayaquil; Peru; press